Analisis Kompetensi Guru Sebagai Bagian Dari Pedagogical Content Knowledge Guru Dalam Menerapkan Pendekatan Saintifik Dalam Program PLPG - Rianasari, Veronika Fitri; Utomo, Beni; Rudhito, Marcellynis Andy (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2016)
AbstractThe purpose of this research is to analyze the competence of teachers as part of the teachers’ pedagogical content knowledge in applying scientific approach in Mathematics PLPG (in-service teacher education and professional training) program rayon 138 Yogyakarta, Indonesia, in 2014. The research method used is descriptive with quantitative approach. The subjects of the study consisted of 23 mathematics teachers including mathematics teachers of junior high school, high school and vocational school from Kebumen, Purworejo, and Magelang. Data was collected by filling in a questionnaire at the beginning and end of the training, observing microteaching activities, and documenting the learning material arranged by PLPG participants. Based on the analysis, it can be concluded that PLPG especially PLPG rayon 138 Yogyakarta, Indonesia, in 2014 gives benefits for the development of teachers’ PCK, especially in terms of teachers’ competence in applying scientific approach. Based on the analysis of learning materials arranged by the teachers and analysis of learning videos, it is known that the majority of the teachers have been able to construct a learning material using scientific approach and implement it properly.  Keywords: teacher’s competence, pedagogical content knowledge, scientific approach, PLPG